THE USE OF LANGUAGES ON JOKOWI’S INSTAGRAM COMMENTS AND ITS IMPLICATIONS ON THE PRESENT NETIZENS’ CHARACTER - Devi Melisa Saragi, S.S., M.A (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2021)
Abstract The study aims at describing the use of languages on Jokowi’s instagram coloums in the context of political propaganda and how it can imply the character of the present netizens. This belongs to a descriptive qualitative research whose data consist of words, phrases and sentences taken from Jokowi’s instagram comments during the 2019 president campaign period. The data collection was conducted by applying the document technique and note taking, while the data analysis was performed by content analysis using inductive method. It is found that there is a deviation of pragmatics in the use of languages towards the political propaganda found on Jokowi’s instagram coloums. The deviation of the pragmatics was a form of sarcasm, hate speech and taboo which were deliberately written in order to attack Jokowi as one of the president candidates for 2019-2024. These pattern of language also implied that present liberal delivering opinion of the Indonesia netizens show a degradation of eastern cultural value especially in using Bahasa. Keywords: Instagram, language use, netizen, pragmatics Abstrak Penenlitian ini bertujuan untuk menjelaskan penggunaan bahasa pada kolom komentar akun instagram Presiden Jokowi dalam konteks propaganda politik serta bagaimana penggunaan bahasa tersebut dapat mengimplikasikan karakter para netizen Indonesia sekarang ini. Penelitian ini merupakan penelitian deskriptif kualitatif yang data−datanya berbentuk kata, frasa dan kalimat diambil dari akun instagram Presiden Jokowi selama kampanye Presiden 2019. Data dikumpulkan melalui teknik catat dan dokumentasi untuk kemudian dianalisis melalui teknik analisis isi dengan menggunakan metode induktif. Hasil penelitian menunjukkan bahwa bahasa yang digunakan para netizen dalam konteks propaganda politik telah mengalami penyimpangan secara pragmatis. Wujud dari penyimpangan tersebut adalah bentuk sarkasme, ujaran kebencian dan bahasa tabu yang digunakan untuk menyerang Jokowi sebagai salah satu kandidat presiden untuk periode 2019−2024. Selain itu, pola penggunaan bahasa ini juga mengimplikasikan bahwa cara para netizen Indonesia mengemukakan pendapat secara bebas menunjukkan adanya penurunan dari nilai−nilai kebudayaan timur terutama dalam penggunaan bahasa. Kata kunci: Instagram, penggunaan bahasa, netizen, pragmatik